Modelling population dynamics and trends in migratory birds from non-standardized multi-species ringing data: the potential of multi-model selection. Issue 3 (3rd July 2021) - Petras, Tina; Vrezec, Al
ABSTRACT: Capsule: Long-term and non-standardized migratory bird ringing data can be used in models controlling variation in bird ringing methodology for reliable population trend estimations. Aims: Bird ringing data usually cover long periods and might reflect long-term population changes. However, they are mainly derived during non-standardized multi-species catching at numerous sites during the autumn migration period. We searched for the best modelling approach to determine reliable species population dynamics and trend estimation models based on annual multi-species bird ringing data. Methods: We used ringing data from the Slovenian Bird Ringing Scheme and selected data in three steps according to temporal, quantitative, and qualitative data selection. Annual indices were constructed based on two types of denominators, ringing days, and ringing totals, vs. a robust model without a denominator. We ran 20 candidate-generalized additive models describing migrating population dynamics for 15 bird species by combining different data selection approaches and denominators. Results: We found that the models were species-specific, although the universal model could also be applied to most species. We propose a general model construction approach for population trend assessments from non-standardized bird ringing data. The estimates obtained by this approach were comparable to the overall European population trends derived from breeding survey data. Conclusions: Bird ringing data from the autumn migration period are a valuable resource for assessing continental scale population trends taking into account the whole population (non-breeders and juveniles included) and even some rare and endangered species, but should be conducted according to standard protocols to ensure reliable statistical inference of population trends.